PENINGKATAN KEMAMPUAN MENARI SISWA DENGAN MENGGUNAKAN METODE KELOMPOK DI KELAS V SD PLUS MARHAMAH - Jauhari Kumara Dewi; Yuliasma Yuliasma; Idawati Syarif (SENDRATASIK UNP, 2013)
Abstract Mostly, teachers’ class management was seen to be lack with appropriate learning methods for the students. In fact, there were numbers of learning methods that were possible to be implemented by teachers in the learning process especially for dancing. One of them was the group method. This research aimed at determining the influence of using this method. The design of research was the class action research. The objects of the research were 24 fifth grade students of SD Plus Marhamah. The learning process was conducted within two cycles. The findings of the research showed that there was an improvement on students’ dancing abilities. It was observed from their increased scores from the first cycle to the second cycle. In the first cycle, students’ dancing average score was 61.87. The score increased in the second cycle to 73.75. It was concluded that the implementation of the group method had successfully improved the fifth grade students’ dancing abilities at SD Plus Marhamah Padang. The improvement was seen from the increased dancing scores gotten by the students.   Kata kunci: Kemampuan Menari, Metode Kelompok